Investigation simulation based on bio-energy local area photosensitizer in increasing dye-sensitized solar cells (DSSC) performance - Supriyanto, Edy; Kartikasari, Henry Ayu; Alviati, Nova; Harsono, Soni Sisbudi; Sutjipto, A. G. E. (Trans Tech Publications, Switzerland, 2020)
The photosensitizer is an important part of Dye-Sensitized Solar Cells (DSSC). Photosensitizers function like photosynthesis by absorbing sunlight and turning it into energy. Photosensitizers also contribute to the efficiency of improving DSSC performance. This research is a continuation of previous research to find a candidate for natural and environmentally friendly photosensitizer (bio-energy) based local area in Indonesia. The photosensitizer used in this simulation is Tagetes erecta, Nyctanthes arbor-tritis, Brassica rapa Sub. Sp pekinensis, Delonix regia, Lawsonia inermis, Callistemon citrinus, and Daucus Carota. The purpose of this simulation is finding several candidates for bio-energy local area photosensitizer that produce high efficiency by displaying J-V curves and P-V curves. The highest efficiency was produced by photosensitizer Tagetes erecta at 1.5% [Voc 0.6385 Volt, 0.00383 A / cm2 Jsc, FF 0.605 and Pmax 0.00148 Watt], while the lowest efficiency was produced by photosensitizer Callistemon citrinus at 1.1% [Voc 0.6162 Volt, Jsc 0.0032 A / cm2, FF 0.557 and Pmax 0,0011 Watts]. These simulation results perform that one of reason give influence at DSSC performance is the absorption coefficient value in each bio-energy local area photosensitizer. The absorption coefficient also determines how much efficiency is produced and how much the photosensitizer's ability to absorb sunlight.